Transformasi Produk Jamu Tradisional Menjadi Bentuk Effervescent sebagai Inovasi Usaha Mikro di Kecamatan Pagu Kabupaten Kediri - Agustia Dwi Pamujiati; Tutut Dwi Sutiknjo; Nugraheni Hadiyanti; Lailatul Azkiyah; Mochammad Shobriansah (PRIMA: Journal of Community Empowering and Services, 2026)
Transformation of Traditional Herbal Medicine into Effervescent Form as an Innovation Strategy for Microenterprises in Pagu District, Kediri Regency. Traditional herbal medicine (jamu) is an Indonesian cultural heritage that plays an important role in maintaining health; however, it still faces limitations in terms of shelf life, taste stability, and attractiveness to younger consumers. Therefore, product innovation is needed to create more modern forms without eliminating its traditional values. This community service activity aimed to improve the knowledge and skills of traditional jamu producers in Pagu Subdistrict, Kediri Regency, through the development of effervescent-based jamu. The method applied was a participatory approach consisting of preparation, counseling, production practice, and evaluation stages. The practical activities included the production of effervescent jamu, packaging, promotion, and market testing, while the evaluation was conducted using pre-test and post-test assessments and a hedonic test involving 20 respondents. The results showed that participants were able to produce three variants of effervescent jamu, namely turmeric tamarind, temulawak honey, and ginger lemongrass. All variants were categorized as “liked,” with average scores above 4.0, where the ginger lemongrass variant achieved the highest acceptance level at 90%. In addition, participants’ knowledge increased by 33.4%. This activity demonstrated that effervescent innovation can enhance skills, product value, and competitiveness of traditional jamu businesses, and has strong potential to be developed as an innovative product based on local wisdom.